Utilisation of Exhausted Coffee Husk as Low-Cost Bio-Sorbent for Adsorption of Pb2+ - Rusnam,; Aninda Tifani Puari,; Nika Rahma Yanti,; Efrizal, (Tropical Life Sciences Research, 2022)
This study utilised a bio-sorbent from exhausted coffee husk (ECHBS) for the removal of ion Pb2+ from an aqueous solution. Four different activation methods were conducted by chemical activation with KOH, H3PO4, ZnCl2, and without chemical activation. In addition, the influence of process parameters such as heating temperature, heating time and heating gradient were investigated. Based on the experimental results, ECHBS without chemical activation (biochar) had the highest Pb2+ ion removal efficiency. The results showed that the heating temperature of 500°C, the heating time of 60 min and the heating rate of 15°C/min were optimum for preparation of the biochar. Under the optimum conditions, the removal efficiency and adsorption capacity reached 99% and 3.3 mg/g, respectively. The experimental data indicated that the adsorption isotherms are well fitted with the Langmuir Equilibrium isotherm model. Furthermore, the adsorption of the biochar follows the pseudo- second-order model. The result obtained from the present study confirmed that exhausted coffee husk is a suitable low-cost bio-sorbent for removing ion Pb2+.